The Influence of Leverage and Firm Size on Firm Value in the Banking Sector Listed on the Indonesia Stock Exchange (IDX) - Dhea Ananda; Riri Mayliza (INVEST : Jurnal Inovasi Bisnis dan Akuntansi, 2025)
Shareholder welfare is often reflected in a company’s value, encouraging firms to innovate in order to enhance their market valuation. This study aims to examine the impact of leverage and company size on the company value of banking sector firms listed on the Indonesia Stock Exchange from 2019 to 2023. A sample of 38 companies was selected using the proportional sampling method. The analysis was conducted using panel data regression. The findings reveal that leverage has a negative and significant effect on company value, while company size does not have a significant effect on company value in the banking sector firms listed on the Indonesia Stock Exchange.